TikTok dan Mediamorphosis: Peran TikTok Sebagai Mesin Pencari Baru untuk Generasi Z - Ramadhina, Annisa Prima; Salsabila, Jihan; Emanuella, Merle (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
This research highlights the changes in the information consumption and search behavior of Generation Z, with a focus on the role of TikTok as a new alternative search engine compared to Google. This research employs the perspective of Mediamorphosis to understand how TikTok has evolved into a platform that functions not only as a social media site but also as a search engine for information retrieval. Using a mixed research method, data were collected through surveys and interviews to explore the behavioral changes of Generation Z in accessing information, with a preference for short-form audio-visual content. The findings indicate that this shift reflects a broader digital cultural change, where the need for fast and personalized information takes precedence, alongside a growing tendency to consume content that is more visual and interactive. These findings provide insights into the development of information search technologies and how social media platforms can alter the way young generations search for and consume information.